Mixed and multi-methods protocol to evaluate implementation processes and early effects of the Pradhan Mantri Jan Arogya Yojana scheme in seven Indian states - De Allegri, Manuela; Srivastava, Swati; Strupat, Christoph; Brenner, Stephan; Parmar, Divya; Parisi, Diletta; Walsh, Caitlin; Mahajan, Sahil; Neogi, Rupak; Ziegler-Wirtz, Susanne; Basu, Sharmishtha; Jain, Nishant (International journal of environmental research and public health, 2020)
In September 2018, India launched Pradhan Mantri Jan Arogya Yojana (PM-JAY), a nationally implemented government-funded health insurance scheme to improve access to quality inpatient care, increase financial protection, and reduce unmet need for the most vulnerable population groups. This protocol describes the methodology adopted to evaluate implementation processes and early effects of PM-JAY in seven Indian states. The study adopts a mixed and multi-methods concurrent triangulation design including three components: 1. demand-side household study, including a structured survey and qualitative elements, to quantify and understand PM-JAY reach and its effect on insurance awareness, health service utilization, and financial protection; 2. supply-side hospital-based survey encompassing both quantitative and qualitative elements to assess the effect of PM-JAY on quality of service delivery and to explore healthcare providers’ experiences with scheme implementation; and 3. process documentation to examine implementation processes in selected states transitioning from either no or prior health insurance to PM-JAY. Descriptive statistics and quasi-experimental methods will be used to analyze quantitative data, while thematic analysis will be used to analyze qualitative data. The study design presented represents the first effort to jointly evaluate implementation processes and early effects of the largest government-funded health insurance scheme ever launched in India.
Gesehen am 12.01.2021